2008
DOI: 10.1029/2007wr006170
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent vadose zone steady state flow: An assessment of its capability to predict transport in a realistic combined vadose zone–groundwater flow system

Abstract: [1] The applicability of an equivalent steady state vadose zone flow model to a realistic transient three-dimensional, heterogeneous, combined vadose zone-groundwater flow system was tested here. Two cases pertinent to semiarid regions and the presence (or absence) of an irrigated crop were analyzed and are presented in detail using the hydraulic properties from the Bet Dagan trench. In addition, the case of a more humid region characterized by additional summer precipitation and soils of different textures wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 72 publications
(87 reference statements)
0
57
1
Order By: Relevance
“…It is a matter of fact that a correct modelling of the spatial variability of the hydraulic properties results in a highly reliable prediction of flow and transport processes (see, e.g., Neuman & Tartakovsky, ; Dagan, Fiori, & Jankovic, , and references therein). In particular, these and other studies (such as those of Russo & Fiori, ; Zarlenga, Fiori, & Russo, ) have emphasized how the spatial variability of a vadose zone eventually can be incorporated within upscaled models. As a consequence, a central problem in the hydrology of a vadose zone is whether the laboratory scale Richards equation t0.1emϑ()Ψ=·[]K()ΨboldE,1emboldE()z+normalΨ, can be used tout court at larger scales (Beven, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a matter of fact that a correct modelling of the spatial variability of the hydraulic properties results in a highly reliable prediction of flow and transport processes (see, e.g., Neuman & Tartakovsky, ; Dagan, Fiori, & Jankovic, , and references therein). In particular, these and other studies (such as those of Russo & Fiori, ; Zarlenga, Fiori, & Russo, ) have emphasized how the spatial variability of a vadose zone eventually can be incorporated within upscaled models. As a consequence, a central problem in the hydrology of a vadose zone is whether the laboratory scale Richards equation t0.1emϑ()Ψ=·[]K()ΨboldE,1emboldE()z+normalΨ, can be used tout court at larger scales (Beven, ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this is not the case in this paper, we note that other parameters used to describe the retention curves, including k r , may have an explicit dependence on the spatial variable x and their variability may also have a strong influence on the flow behavior (see, e.g., Russo and Fiori [2008] and literature therein).…”
mentioning
confidence: 75%
“…Quantitative descriptions of solute transport in the combined flow system are essential for the analysis of groundwater contamination, and are fundamental prerequisite for risk assessment of groundwater contamination hazard. For given boundary and initial conditions and for a soil of a given texture, water flow and solute transport in the combined flow system are controlled by the heterogeneity of the soil hydraulic properties as demonstrated by simulations [e.g., Foussereau et al , 2001; Russo et al , 2001; Russo and Fiori , 2008] and analyzed in a theoretical stochastic framework [e.g., Destouni and Graham , 1995; Russo and Fiori , 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of an equivalent steady state (ESS) vadose zone flow which is able to represent the transient flow process was investigated in recent years by a few authors, e.g., the one‐dimensional, homogeneous numerical analysis of Salvucci and Entekhabi [1994], and the three‐dimensional, heterogeneous numerical analysis of Russo and Fiori [2008]. In particular, the latter showed that the cumulative flux of the net applied water, Qnaw = Qin − Qet , (where Qin is the cumulative water flux entering the soil surface, Qet = Qtr + Qev , and Qtr and Qev are the cumulative fluxes of the actual transpiration and evaporation, respectively), can be used as an approximation for the cumulative flux crossing the water table, Qwt .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation